2018
DOI: 10.1101/399022
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the feasibility of saltational evolution

Abstract: One of the key tenets of Darwin's theory that was inherited by the Modern Synthesis of evolutionary biology is gradualism, that is, the notion that evolution proceeds gradually, via accumulation of "infinitesimally small" heritable changes 1,2 . However, some of the most consequential evolutionary changes, such as, for example, the emergence of major taxa, seem to occur abruptly rather than gradually, as captured in the concepts of punctuated equilibrium 3,4 and evolutionary transitions 5,6 . We examine a math… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…This likely explains the observations of repeated mutations putatively contributing to adaptive variation for these loci, as observed for both STRs in A. thaliana ( Figure 1E) and TEs in Drosophila [60]. Further theoretical work suggests that multi-mutation "jumps" become possible with elevated mutation rates relative to selection, changing dynamics of evolution on rugged fitness landscapes [43,61].…”
Section: High Mutation Rates and Evolutionary Geneticsmentioning
confidence: 65%
“…This likely explains the observations of repeated mutations putatively contributing to adaptive variation for these loci, as observed for both STRs in A. thaliana ( Figure 1E) and TEs in Drosophila [60]. Further theoretical work suggests that multi-mutation "jumps" become possible with elevated mutation rates relative to selection, changing dynamics of evolution on rugged fitness landscapes [43,61].…”
Section: High Mutation Rates and Evolutionary Geneticsmentioning
confidence: 65%
“…This likely explains the observations of repeated mutations putatively contributing to adaptive variation for these loci, as observed for both microsatellites in A. thaliana ( Figure 1E) and TEs in Drosophila [48]. Further theoretical work has suggested that multi-mutation "jumps" become possible with elevated mutation rates relative to selection, changing dynamics of evolution on rugged fitness landscapes [12,49].…”
Section: High Mutation Rates and Evolutionary Geneticsmentioning
confidence: 67%